Nursing care for people with Parkinson's disease in Primary Health Care: a scoping review protocol - Nunes, Simony Fabíola Lopes (2021)
Aim: to identify in the literature the main topics investigated about nursing care for people with Parkinson's disease in primary health care. Method: this is a scope review protocol carried out according to the Joanna Briggs Institute methodology and the Preferred Reporting Items for Systematic Reviews Checklist and the Meta-Analyzes extension for Scoping Reviews (PRISMA-ScR). This investigation will follow these steps: protocol, eligibility criteria, information sources, research strategy, selection of sources, data extraction, data analysis, and presentation of results. Its review question is “What are the nursing cares provided to people with Parkinson's disease in primary health care as described in the literature?”. To identify the relevant documents, the following bibliographic databases will be used: Public Medline, Cumulative Index to Nursing & Allied Health Literature, Web of Science, SciVerse Scopus, Nursing Database, Latin American and Caribbean Literature in Health Sciences, and Scientific Electronic Library Online. The results of this selections flow will be presented using figures as outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes. Results: the results of this study will shed light on the main researched areas of care and nursing interventions aimed at people with Parkinson's disease in primary healthcare. Conclusion: This study is the first step in a research agenda that aims to deepen the analysis and systematization of nursing care for people living with Parkinson's disease.